ULTIMATE PREDATOR-PEDIA : THE MOST COMPLETE REFERENCE EVER - Wilsdon, Christina (Washington, DC : National Geographic Kids, 2018)
"Reference book for children about all predators in the animal world"--
Includes index
Keywords: Predatory animals -- Juvenile literature; Predatory animals; Reference works; Picture books; Instructional and educational works; Encylopedia